Resistance training for persons with osteoarthritis and rheumatoid arthritis - Ronai, P.; Sorace, P.; LaFontaine, T. (Strength and Conditioning Journal, 2008)
Arthritic conditions affect more than 40 million americans and are a major cause of physical disability. Resistance training has been found to improve muscular performance in persons with osteoarthritis and rheumatoid arthritis. This column discusses the benefits of resistance training in persons with osteoarthritis and rheumatoid arthritis and provides general suggestions for developing safe, effective resistance training programs. © National Strength and Conditioning Association.
Keywords: dept.hms

The performance-level model of hospital decontamination preparedness. - Phelps, Scot; Doering, Garrett (American journal of disaster medicine, 2008)
OBJECTIVE: Describe a multilevel model of decontamination capacity for hospitals., DESIGN: Descriptive model., SETTING: Acute care hospitals with decontamination responsibilities., PATIENTS, PARTICIPANTS: None., INTERVENTIONS: None., MAIN OUTCOME MEASURE(S): None., RESULTS: This multilevel model of defining decontamination capacity would allow more realistic assessment of current capacity, allow for fluctuating service levels depending on time of day, incorporate realistic ramp-up and ramp-down of decontamination services, allow for a defined fall-back decontamination model should decontamination processes fail, allow hospitals to define long-term decontamination service level goals, and allow better understanding of when and why to focus on low-risk/low-resource patients rather than high-risk/high-resource patients., CONCLUSIONS: This multiple-level model would allow for more realistic and effective hospital-based decontamination service models and should become part of the national decontamination paradigm.
Keywords: *Decontamination/st [Standards]; *Disaster Planning/st [Standards]; *Emergency Service, Hospital/og [Organization & Administration]; *Hospital Administration/st [Standards]; *Models, Organizational; Decontamination; Disaster Planning; Emergency Service, Hospital; Hospital Administration; Hospitals; Hospitals/st [Standards]; Humans; MLCS; MLOWN; Models, Organizational; Terrorism; article; dept.hms; disaster planning; emergency health service; hospital; hospital management; human; nonbiological model; organization and management; standard; terrorism; waste management